Pengaruh Variasi Konsentrasi Perekat Tanah Liat Pada Pembuatan Pupuk Organik Granul (POG) Dari Limbah Lumpur IPAL Pabrik CPO (Crude Palm Oil ) - Fatiha Rizqa; Elvi Yenie; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Limitations possessed by compos in the form of bulk are in the process of spreading easily carried by the wind and easily drift when carried by the water, and requires a large space during storage, and difficult in the process of distribution. Therefore it is necessary to conduct a study that examines the physical quality of a solid organic fertilizer one of them is by making Granul Organic Fertilizer (POG). This study aims to observe the effect of adhesive concentration on physical quality (POG) produced. The methodology used in this research is variation of 5%, 10%, 15%, and 20% clay adhesive by calculating the value of bulk density, percentage of granule size (2-5 mm), durability value, water absorption value, time dispersion. The best POG quality is on clay adhesive 20%Keywords: Organic fertilizer granules (POG), clay, particle size